Reading Scripted Dialogue: Pretending to Take Turns. Issue 3 (15th March 2020) - Aruffo, Christopher
ABSTRACT: This study examined conversational turn-taking when reading scripted dialogue versus having a spontaneous conversation. When reading, listeners waited until speakers' turns had been completed before moving to start their own turns, and gap lengths between turns were longer than those of spontaneous, natural conversation. Theatrical performance training and studying the scripts worked to reduce readers' gap lengths but not to the level of natural conversation, because all readers persisted in waiting for the ends of speakers' scripted turns instead of coming in earlier as they had done in natural conversation. Participants were therefore not negotiating for the conversational floor when reading but were instead working to realize the prescribed sequence of utterances. These results advise consideration when interpreting turn-taking findings drawn from participants reading scripted materials, because readers did not engage in the collaborative, interactive turn taking that is characteristic of spontaneous conversation. Instead, readers were essentially pretending to take turns.